Revisiting the Mechanisms of ENSO Response to Tropical Volcanic Eruptions - Pausata, Francesco S. R.; Zhao, Yang; Zanchettin, Davide; Caballero, Rodrigo; Battisti, David S. (Geophysical Research Letters, 2023)
Abstract Stratospheric volcanic aerosol can have major impacts on global climate. Despite a consensus among studies on an El Niño‐like response in the first or second post‐eruption year, the mechanisms that trigger a change in the state of El Niño‐Southern Oscillation (ENSO) following volcanic eruptions are still debated. Here, we shed light on the processes that govern the ENSO response to tropical volcanic eruptions through a series of sensitivity experiments with an Earth System Model where a uniform stratospheric volcanic aerosol loading is imposed over different parts of the tropics. Three tropical mechanisms are tested: the “ocean dynamical thermostat” (ODT); the cooling of the Maritime Continent; and the cooling of tropical northern Africa (NAFR). We find that the NAFR mechanism plays the largest role, while the ODT mechanism is absent in our simulations as La Niña‐like rather than El‐Niño‐like conditions develop following a uniform radiative forcing over the equatorial Pacific. , Plain Language Summary Volcanic eruptions emit large quantity of sulfate aerosol up to the stratosphere. Such aerosol can alter global climate by interacting with solar radiation and in turn modifying atmospheric and ocean circulation. In particular, volcanic aerosol can alter the state of the El Niño‐Southern Oscillation (ENSO), the major mode of tropical climate variability. However, the mechanisms that trigger a change in the ENSO state following volcanic eruptions are still debated. In this study, we use an Earth System Model to revisit the main mechanisms that have been proposed to alter ENSO, causing positive temperature anomalies over the equatorial Pacific (EqPAC) Ocean. We tested three mechanisms: the “ocean dynamical thermostat” (ODT); the cooling of the Maritime Continent; and the cooling of tropical northern Africa (NAFR). Our experiments show that the NAFR mechanism plays the largest role, while the ODT mechanism is absent in our simulations as cold rather than warm develop over the EqPAC Ocean following the applied volcanic forcing. , Key Points Radiative cooling by volcanic aerosol over the tropical northern Africa triggers El Niño‐like conditions via atmospheric circulation changes The “ocean thermostat mechanism” is absent in our simulations when a uniform aerosol forcing is applied over the equatorial Pacific (EqPAC) The Maritime Continent cooling mechanism is not at play when the aerosol forcing extends over the entire EqPAC